2009
DOI: 10.1167/iovs.08-2577
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Adaptive Modification of Dynamic Ocular Accommodation

Abstract: Purpose Indirect observations suggest that the neural control of accommodation may undergo adaptive recalibration in response to age-related biomechanical changes in the accommodative system. However, there has been no direct demonstration of such an adaptive capability. This investigation was conducted to demonstrate short-term adaptation of accommodative step response dynamics to optically induced changes in neuromuscular demands. Methods Repetitive changes in accommodative effort were induced in 15 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
1
15
1
Order By: Relevance
“…The first paradigm replicated the adaptation method used by Bharadwaj et al (2009), their “increasing paradigm,” in which the focus stimulator first stepped from 0 to 2D and after 350 msec stepped from 2D to 4D. Bharadwaj et al did not test to see whether a double step was necessary for adaptation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first paradigm replicated the adaptation method used by Bharadwaj et al (2009), their “increasing paradigm,” in which the focus stimulator first stepped from 0 to 2D and after 350 msec stepped from 2D to 4D. Bharadwaj et al did not test to see whether a double step was necessary for adaptation.…”
Section: Methodsmentioning
confidence: 99%
“…Bharadwaj, Vedamurthy and Schor (2009) did not examine patients undergoing VT but examined the ability of young subjects (age 18–34) to modify the dynamics of accommodation using a paradigm which was designed to mimic the type of changes in compliance of the ocular lens that occur with age. These researchers pointed out that, even though the lens becomes less compliant during nascent presbyopia, the dynamics of accommodation change much less than might be expected (Heron, Charman & Schor, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that voluntary control of accommodation can be learned and transferred to a variety of conditions, 14,15 and objective improvements in the dynamics 16 and accuracy of accommodation following vision therapy have been documented. 17,18 …”
mentioning
confidence: 99%
“…In addition, the dynamics of human accommodation involve peak velocities in excess of 12 diopters/sec [9,10] and the accommodative state of the eye is variable even during steady fixation [11]. Experimental OCT systems with line rates in the MHz range [12,13] can significantly reduce motion artifacts, but associated increases in complexity and cost may limit their clinical applications.…”
Section: Introductionmentioning
confidence: 99%